Phylogenetic relationships among the Asian tortoises of the genus Indotestudo (Reptilia: Testudines: Testudinidae) - Iverson, John B.; Spinks, Phillip Q.; Shaffer, H. Bradley; McCord, P. William; Das, I. (Centre for Herpetology, Madras Crocodile Bank Trust, 2001)
Based on variation in 1094 bp of the mitochondrial cytochrome b gene among members of the genus Indotestudo from southern Asia ( I. elongata ), south-western India ( I. travancorica ), and eastern Indonesia ( I. forstenii ), I. travancorica is most similar genetically to I. elongata (3.7% divergence), and strongly divergent from I. forstenii (5.5 to 5.9%). Individuals of I. forstenii with and without a nuchal scute differ genetically at less than 0.7%. Our analysis offers no support for the hypothesis that Indonesian populations of I. forstenii represent introductions of I. travancorica from India. The recognition of three nominal species ( I. elongata, I. forstenii and I. travancorica ) in the genus is thus warranted